New Cd(ii) coordination polymers bearing Y-shaped tricarboxylate ligands as photocatalysts for dye degradation. Issue 36 (25th August 2021) - Du, Lin; Lu, Lu; Shi, Chuncheng; Wang, Hong-Yan; Wang, Jun; Singh, Amita; Kumar, Abhinav
Abstract : Two Cd(ii ) coordination polymers derived from a Y-shaped tricarboxylate ligand were synthesized and their photocatalytic properties against decomposition of methylene blue were investigated experimentally and computationally. Abstract : Coordination polymers (CPs) are an assorted class of multidimensional materials which can be employed as photocatalysts against the photodegradation of toxic aromatic dyes existing in wastewater discharge. Herein, two new coordination polymers with formulas [Cd3 (L)2 (μ2 -H2 O)(H2 O)·2H2 O] (1 ) and [Cd(HL)(H2 O)(phen)·H2 O] (2 ) have been derived from Y-shaped tricarboxylate ligand 1, 3, 5-tris(4-carbonylphenyloxy)benzene (H3 L) and 1, 10-phenanthroline (phen) as a co-ligand. The single crystal X-ray diffraction studies revealed that 1 presents a 3D pillar-layer framework, which contains a 1D stair-type chain and 2D layer. CP 2 displays wave-like 1D chains which link to each other to create a 2D architecture through hydrogen-bonding interactions. The introduction of the chelating N-donor ligand led to significant differences in the final frameworks. Both CPs exhibited efficient photocatalytic performance for the degradation of organic dyes viz. methyl violet (MV), methyl orange (MO), methylene blue (MB) and rhodamine B (RhB) under UV irradiation. Moreover, a possible photocatalytic mechanism via trapping experiments of active species has been proposed. In addition, a mechanistic study towards better understanding of the photocatalytic degradation of dyes has been accomplished through LC-MS studies. Also, computationally using band gap calculations, the probable mechanistic pathway has also been proposed which has been further corroborated with Hirshfeld surface analysis.